Rumen metabolism, carcass traits and meat quality in goats fed blend of canola oil and palm oil - Dauda, Adeyemi Kazeem (2015)
Consumption of ruminant meat has been implicated in the incidence of chronic diseases in human due to the imbalance in its fatty acid (FA) profile. This justifies the need to modify the FA composition of ruminant meat. Dietary supplementation of unsaturated fats is an effective strategy for modifying the FA composition of ruminant meat. However, unsaturated fats could have detrimental effects on rumen microbial metabolism and meat quality. The use of dietary fat blends has been accentuated as a cheaper and readily available alternative for modifying tissue lipids in ruminants compared with rumen inert fats. Nonetheless, the impact of fat blends on rumen metabolism has been highly variable and inconsistent and its effects on meat quality remain obscure. Thus, there is need for specific studies in different production systems to permit tailored decisions and informed choices in the utilization of fat blends in ruminant nutrition. Due to the FA composition and antioxidant contents of canola and palm oils, this study was conducted to examine the effects of blend of canola oil and palm oil on in vitro and in vivo rumen metabolism, nutrient intake and digestibility, growth performance, serum biochemistry, carcass attributes and meat quality in goats. The study was conducted in two phases. The first phase consisted of two in vitro experiments. The first in vitro experiment evaluated the effects of blends of canola oil (CO) and palm oil (PO) and forage (F) to concentrate (C) ratios on rumen fermentation and apparent biohydrogenation (BH) of fatty acids. The treatments included three concentrate to forage (oil palm fronds,OPF) ratios (C:F; 75:25, 50:50 and 25:75) and six blends of canola oil and palm oil (CO:PO; 0:0, 100:0, 80:20, 50:50, 20:80 and 0:100) supplemented at 5% of the dry matter (DM) of the substrate and incubated at 39 oC for 48 h. The pH declined (P< 0.05) while the gas production and volatile fatty acids (VFA) increased as the C:F increased in the control (oil-free) substrates compared with the oil-based substrates. The acetate and methane concentrations were lower (P< 0.05) while the propionate was higher in oil-based substrates than the control substrates. Regardless of the C:F, oil supplementation decreased gas production, VFA, DM and organic matter (OM) digestibilities, saturated fatty acids (SFA), and BH of C18:3n-3 and C18:2n-6, and enhanced the polyunsaturated fatty acids (PUFA) and BH intermediates. There were significant interactions between C:F and CO:PO for gas production, rumen fermentation, and BH of FA. The combination of 50:50, C:F and 80:20, CO:PO yielded higher concentration of unsaturated FA and had minimal adverse effects on rumen fermentation. The second in vitro trial investigated the effects of graded levels of 80% canola oil and 20% palm oil (BCPO) on rumen fermentation and BH of FAs. The BCPO was supplemented to the basal substrate consisting of 50% concentrate and 50% OPF at the rate of 0, 2, 4, 6, and 8%. Supplementation of BCPO did not affect (P> 0.05) gas production and rumen fermentation. Nonetheless, increasing level of BCPO enhanced (P<0.05) the BH of C18:1n-9 but decreased (P<0.05) the BH of C18:2n-6 and C18:3n-3. After 24 h incubation, the concentration of SFA decreased (P<0.05) while that of PUFA and BH intermediates increased (P<0.05) with increasing level of BCPO. The second phase of the study assessed the nutrient intake and digestibility, growth performance, rumen metabolism, serum biochemistry, carcass traits, tissue lipids and meat quality in goats fed diets supplemented with graded levels of BCPO. Thirty Boer crossbred bucks (4-5 months old and BW, 20.53±0.6 kg) were randomly assigned to diets containing 0, 4 and 8% BCPO, fed daily for 100 d and slaughtered. Diet had no effect (P> 0.05) on growth performance and feed efficiency in goats. Dietary BCPO did not affect the intake and digestibility of nutrients except ether extract. The total VFA, acetate, butyrate and methane concentration decreased (P<0.05) with increasing level of BCPO in diet. However, propionate; ammonia nitrogen and rumen pH did not differ (P> 0.05) among the treatments. The populations of total protozoa and methanogens were lower (P< 0.05) while the populations of total bacteria, Ruminococcus albus, Fibrobacter succinogenes and Ruminococcus flavefaciens were higher (P< 0.05) in the oil-fed goats than the control goats. The ruminal proportion of C18:3n-3 and total FA increased (P< 0.05) while the proportion of C18:2n-6 decreased (P< 0.05) with increasing level of BCPO in diet. Diet had no effect on serum antioxidant enzyme (AE) activities and lipid oxidation. Goats fed 4 and 8% BCPO had higher (P< 0.05) serum total cholesterol and HDL cholesterol, n-3 FA and α and γ-tocopherol than the control goats. Dietary BCPO had no effect (P> 0.05) on carcass and non-carcass components but induced significant changes in the FA composition of omental, perirenal and mesentery adipose tissues in goats. Dietary BCPO beneficially altered the FA composition of longissimus lumborum, semimembranosus, infraspinatus and gluteus medius muscles, kidney and liver in goats. Dietary BCPO had no effect on tissue AE activities. However, goats fed 4 and 8% had higher tissue carotenoids and tocopherols over a 7 d postmortem chill storage compared with the control goats. Diet had no effect on the physicochemical and sensory properties but enhanced the oxidative stability of lipid, myoglobin and myofibrillar proteins in chevon over chill storage. Postmortem ageing had significant impact on the oxidative stability of myofibrillar proteins, lipid and myoglobin in goats. Dietary supplementation of BCPO can be used to enhance the beneficial fatty acids in muscles and offal without compromising rumen microbial metabolism, growth performance, serum biochemistry, carcass traits and meat quality in goats.